Strategi Rekrutmen Peserta Didik Di SMP Karya Bunda - Tri Wulan Hasibuan; Fitri Hayati; Nasrul Syakur Chaniago (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
In the current era of globalization, there is a lot of competition from various schools or madrasas, to offer the best quality from their institutions. This can be seen from the various forms of promotion and strategy, moreover educational institutions with a private background are certainly required to have higher quality and competitiveness compared to other educational institutions, especially those with a state label. This research in general, aims to describe (1) how the recruitment of students is carried out at Karya Bunda Middle School (2) What is the strategy used by Karya Bunda Middle School in recruiting new students (3) What are the obstacles faced by the school in the student recruitment process at Karya Bunda Middle School. This research uses descriptive research with a qualitative approach. The subjects in this study were the principal, educators, students, education staff, and two students. Data collection techniques through observation, interviews and documentation. Data validation techniques with research extension, increased persistence, and triangulation. The results of this study indicate (1) the implementation of student recruitment with technical instructions from the Education Office, the recruitment process does not have selection and applicant tests only need to pay administrative costs and have actually passed SD (2) The strategy used in recruiting students is a promotion strategy, namely a strategy from door to door, distributing brochures and placing advertisements on social media, visiting SD/MI, community activities, and working with students (3) in the process constraints the recruitment of these students is due to limited classroom space, unable to compete with the country and less desirable.